PENERAPAN PENGGUNAAN MEDIA BERBASIS YOUTUBE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA (SENI TARI) SISWA KELAS IV SD NEGERI GRONG-GRONG KABUPATEN PIDIE - Misratul Aula; Aida Fitri; Mislinawati (Jurnal Binagogik, 2025)
In arts and culture learning (dance), student learning outcomes are still relatively low due to the lack of student involvement in the teaching and learning process. The problem formulation in this study is how student activities and learning outcomes are affected by the application of YouTube as a learning medium in arts and culture learning (dance) on the theme of recognizing the environment through dance. This study investigates the implementation of YouTube-based media in enhancing student engagement and learning outcomes in Dance Art education, specifically the topic "Recognizing the Environment through Dance" for fourth-grade students at SD Negeri Grong-Grong. Conducted on June 17, 2025, the study involved 15 participants and employed a descriptive qualitative approach. Data were collected through classroom observations and written assessments. Findings indicate that student learning activities ranged from high to very high levels, characterized by enthusiasm, active participation, and improved comprehension through video content. The post-test results showed that the majority of students achieved good to excellent performance, with an average score of 86.66. The use of YouTube as an instructional medium significantly supported students’ understanding of dance movements, sustained their attention, and fostered a more engaging and meaningful learning experience. Despite some technical limitations—such as unstable internet connections and lack of supporting devices—the study confirms the effectiveness of multimedia learning and highlights the importance of integrating digital media in arts education to enhance both student involvement and academic achievement.